1997
DOI: 10.1111/j.1834-7819.1997.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tooth‐related factors on the shear bond strengths obtained with CO2 laser conditioning of enamel

Abstract: Carbon dioxide (CO 2 ) lasers are capable of producing surface irregularities in human enamel which resemble those resulting from etching of enamel with orthophosphoric acid. This report presents the results of a laboratory study which examined the effect of selected tooth-related variables on shear bond strength between a current generation bonding agent (Scotchbond MultiPurpose) and acid-etched or laser-conditioned human enamel. There were no significant differences in shear bond strength between human maxil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 10 publications
0
20
1
3
Order By: Relevance
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
“…Bonding/adhesive strength studies Table 3 depicts the 17 in vitro studies reviewed in this category (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). Three studies tested only human and bovine enamel (65)(66)(67).…”
Section: Dental Erosion/abrasion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some researchers 15,16 agree that laser etching is not suitable for etching enamel, others [17][18][19] reported that laser irradiation can be used to etch tooth enamel. In our opinion, the contrary findings were due to the different outputs and experimental designs of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Bazı çalıĢmalarda kumlama ve lazer uygulamalarının asit uygulanmasına alternatif olacağı görüĢü var iken, baĢka çalıĢmalarda bu görüĢün tersi iddialar ortaya atılmıĢtır. [17][18][19][20][21][22][23][24][25][26][27] Sonuç olarak, bugüne kadar yapılan farklı çalıĢmalardan ortaya çıkan ortak bir görüĢ mevcut değildir. Bu nedenle, bu çalıĢma dört farklı pürüzlendirme yönteminin ortodontik braketlerin mineye makaslama bağlanma dayanımı üzerine etkisini incelemeyi amaçlamaktadır.…”
Section: Gġrġġunclassified